1054 Physical workload exposure threshold in cumulative-trauma disorders useful for primary prevention and for causal assessment: a 12.5 y follow-up cohort study. (24th April 2018) - Alvarez-Rincón, DA; Perez, N
Abstract : Introduction: Cumulative-Trauma Disorders (CTD) are major loss causes in labour environments through the world, but few is known about quantitative robust and reliable workload exposure limits. The aim of this research was to define shoulder repetitiveness exposure threshold by assessing the risk of rotator cuff, biceps and bursal injuries (dependent variable) in a cohort of workers. Methods: A retrospective cohort study was assembled with workers from different positions. Inclusion/exclusion criteria were rigorously applied. Clinical and sociodemographic variables were extracted from each worker´s clinic history (age, sex, handedness, civil status, academic level, menopause, mood disorders, hyperglycemia, hyperuricema, and abnormal globular-sedimentation velocity, rheumatoid factor, reactive-c protein, thyroid-stimulating hormone and anti-nuclear antibodies). Dependent variable was obtained using nuclear magnetic resonance, ultrasound and/or surgical reports. Shoulders workload was assessed independently getting cumulative-exposure time to repetitive motions, which was adjusted by rest/break periods, maternity/paternity leave, vacations and all-causes medical absences (effective cumulative-exposure time). The exposure threshold was acquired using an adjusted multivariate Weibull regression modelling in order to control confusing effects. A Huber's M-estimator was performed warranting robust results, correcting both shoulders non-completely independent measures (two shoulders by worker). Results: 656 shoulder workloads were analysed. At following-end, following-span median was 12.5 years, age median was 42 years, 60% were women, 85% had non-university academic level and 77% had non-administrative positions. Age, handedness, academic level, work type and mood disorders were proved as significant or as confounding covariates within the final model. 4 × 10 3 cumulative-effective working hours of shoulder repetitiveness exposure was established clearly as threshold (adjusted HR=1.93; 95% CI: 1.04 to 3.59). Discussion: Taking real action in developing world should be addressed towards effective primary prevention, which means that no worker should be exposed more than repetitiveness threshold, in order to eliminate shoulder´s CTD. On the other hand, proved threshold overpassing shall confirm work-related causation in injured workers within compensation processes.